Load Modulation Affects Pediatric Lower Limb Joint Moments During a Step-Up Task - Vatsala Goyal; Keith E. Gordon; Theresa Sukal-Moulton (Biomechanics)
Introduction: Performance in a single step has been suggested to be a sensitive measure of movement quality in pediatric clinical populations. Although there is less information available in children with typical development, researchers have postulated the importance of analyzing the effect of body weight modulation on the initiation of stair ascent, especially during single-limb stance where upright stability is most critical. The purpose of this study was to investigate the effect of load modulation from −20% to +15% of body weight on typical pediatric lower limb joint moments during a step-up task. Methods: Fourteen participants between 5 and 21 years who did not have any neurological or musculoskeletal concerns were recruited to perform multiple step-up trials. Peak extensor support and hip abduction moments were identified during the push-off and pull-up stance phases. Linear regressions were used to determine the relationship between peak moments and load. Mixed-effects models were used to estimate the effect of load on hip, knee, and ankle percent contributions to peak support moments. Results: There was a positive linear relationship between peak support moments and load in both stance phases, where these moments scaled with load. There was no relationship between peak hip abduction moments and load. While the ankle and knee were the primary contributors to the support moments, the hip contributed more than expected in the pull-up phase. Discussion: Clinicians can use these results to contextualize movement differences in pediatric clinical populations, including in those with cerebral palsy, and highlight potential target areas for rehabilitation for populations such as adolescent athletes.